Konsep Zuhud al-Qushayrî dalam Risâlah al-Qushayrîyah - Fudholi, Moh. (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2011)
The purpose of this study is to gain a comprehensive information about the concept of zuhd that is explained in Risâlah al-Qushayrîyah authored by al-Qushayrî. The study is formulated wihin the concept and history of zuhd, namely zuhd as a maqâm (stage) and zuhd as an akhlâq (moral). The research uses interpretation method. According to al-Qushayri, zuhd is resignation to Allah Himself. The correct zuhd will lead to virtuous morals.